Are Alternative Work Arrangements a Substitute for Standard Employment? Evidence from Worker-Level Data - Bernardo Fanfani; Filippo Passerini (Institute of Labor Economics (IZA), 2024)
This study analyses the impact of vouchers, an Italian alternative work arrangement, on earnings of atypical workers. We investigate whether this form of very flexible casual work substitutes for income from more standard labor contracts and from employment insurance programs. We rely on panel data estimators and a difference-in-differences specification that exploits a plausibly exogenous variation in the use of vouchers. Results show that around 50% of reductions in earnings from vouchers can be compensated by an increase in income derived from standard labor contracts and, to a much lower extent, by higher income from employment insurance. However, when considering a sub-sample of intensive users, only around 10% of losses in earnings from vouchers are compensated by other income sources. Thus, policies aiming at restricting or abolishing alternative work arrangements should be complemented by targeted interventions, particularly on intensive users, in order to mitigate the short-run earning losses of atypical workers.
Keywords: J24; J22; D12; C13; C21; 330; alternative work arrangements; policy evaluation; labor supply; cross-income elasticity; sample selection; difference-in-differences; event-study